2022
DOI: 10.1101/2022.06.26.497661
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Six-Dimensional Single-Molecule Imaging with Isotropic Resolution using a Multi-View Reflector Microscope

Abstract: We report a radially and azimuthally polarized multi-view reflector (raMVR) microscope for precise imaging of the 3D positions and 3D orientations of single molecules (SMs, 10.9 nm and 2.0° precisions using 5000 photons). These precisions are ∼1.5 times better than those of existing methods for SM orientation-localization microscopy. The raMVR microscope achieves 6D super-resolution imaging of Nile red (NR) molecules transiently bound to 150 nm, 350 nm, and 1 µm-diameter lipid-coated spheres, accurately resolv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Experimental 5D imaging of amyloid fibrils Amyloid aggregates are linked to various pathological diseases, e.g., Parkinson's and Alzheimer's disease [44,45]. Previous studies have shown that upon binding transiently to amyloid fibrils, Nile red (NR) orients itself parallel to their backbones [3,4,15]. Thus, imaging NR enables us to validate Deep-SMOLM's performance for 5D SM imaging of orientations and positions from experimental data.…”
Section: D Imaging Of Simulated Biological Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental 5D imaging of amyloid fibrils Amyloid aggregates are linked to various pathological diseases, e.g., Parkinson's and Alzheimer's disease [44,45]. Previous studies have shown that upon binding transiently to amyloid fibrils, Nile red (NR) orients itself parallel to their backbones [3,4,15]. Thus, imaging NR enables us to validate Deep-SMOLM's performance for 5D SM imaging of orientations and positions from experimental data.…”
Section: D Imaging Of Simulated Biological Fibersmentioning
confidence: 99%
“…Researchers have used molecular orientations [1] to elucidate the architectures of amyloid aggregates [2][3][4], the organization of proteins in actin filaments [5,6], and changes in lipid membrane polarity and fluidity induced by cholesterol [4,7,8]. To effectively use limited photon budgets in single-molecule (SM) imaging, dipole-spread functions (DSFs), i.e., the vectorial extension of the optical microscope's point-spread function, must be engineered to encode additional information about a molecule's 3D orientation [5,[9][10][11][12][13][14][15]. However, simultaneously estimating the 3D orientation and position of an emitter is challenging because 1) it is difficult to estimate SM parameters in 5-dimensional space (3D orientation, wobble, 2D position) without getting trapped in local minima instigated by severe Poisson shot noise [4,14],…”
Section: Introductionmentioning
confidence: 99%
“…40% 胆固醇的 DPPC SLBs 瞬间结合成像, 根据测得的角度对线进行定向和颜色编码 Fig. 8 Concept of the raMVR SMOLM [43] . [20] ; (b) comparison of diffractionlimited fluorescence images with Richardson -Lucy deconvolution results and SPoD images; (c) schematic diagram of P -TIRF [22] ; (d) P -TIRF imaging, Ring TIRF imaging, curve fitting of fixed microtubules, and comparison of Boulanger method and P -TIRF reconstruction depth map…”
mentioning
confidence: 99%
“…Fig.8Concept of the raMVR SMOLM[43] . (a) Schematic of the raMVR microscope; (b) the raMVR pyramidal mirrors; (c) NR molecules transiently binding to DPPC SLBs containing 40% cholesterol surrounding a silica sphere, lines are oriented and colourcoded according to the measured polar angle…”
mentioning
confidence: 99%